Myelin Water Fraction Imaging of the Brain in Children with Prenatal Alcohol Exposure. (8th April 2019) - McLachlan, Kaitlyn; Vavasour, Irene; MacKay, Alex; Brain, Ursula; Oberlander, Tim; Loock, Christine; Reynolds, James N.; Beaulieu, Christian
Abstract : Background: Prenatal alcohol exposure (PAE) is linked to alterations of cerebral white matter, including volume and nonspecific diffusion magnetic resonance imaging (MRI) indices of microstructure in humans. Some animal models of PAE have demonstrated myelination deficiencies, but myelin levels have not yet been evaluated in individuals with PAE. Multiecho T2 MRI offers a quantitative method to estimate myelin water fraction (MWF; related to myelin content) noninvasively, which was used here to evaluate brain myelination in children with PAE. Methods: Participants with PAE ( n  =   10, 6 females, mean age 13.9 years, range 7 to 18 years) and controls ( n  =   14, 11 females, mean age 13.2 years, range 9 to 16 years) underwent 3T MRI of the brain. T2 images (15 minutes acquisition for 32 echoes) were used to create MWF maps from which mean MWF was measured in 12 regions of interest (ROIs) including 8 in white matter and 4 in deep gray matter. Results: As expected, across the combined sample, MWF was highest for major white matter tracts such as the internal capsule and genu/splenium of the corpus callosum (10 to 18%) while the caudate and putamen had MWF less than 5%. Mean MWF was similar across 11/12 brain white and gray matter regions for the PAE and control groups (L/R internal capsule, major forceps, putamen, caudate nucleus, L minor forceps, genu and splenium of corpus callosum). In the PAE group, MWF was positively correlated with age in the genu of corpus callosum and right minor forceps, notably 2 frontal tracts. Conclusions: Given comparable MRI‐derived myelination fraction measures in PAE relative to controls, white matter alterations shown in other imaging studies, such as diffusion tensor imaging, may reflect microstructural anomalies related to axon caliber and density. Abstract : A novel Magnetic Resonance Imaging (MRI) method was used to assess myelin water fraction in children and adolescents with prenatal alcohol exposure (PAE) compared to controls. The myelin water fraction was similar between PAE and controls, suggesting that white matter alterations shown in other brain imaging studies may reflect micro‐structural anomalies related to axon caliber and density.